Commercial banks as a mechanism against financing terrorism - Dimitrova, T. (Економічний вісник Донбасу, 2017)
In the process of globalization, the need to block financial flows to terrorist organizations is becoming more and more tangible. The fight against terrorist financing is becoming a national and supranational priority, and credit institutions are among the main mechanisms for committing such crimes, and are therefore covered by numerous regulations and institutions concerning their role in controlling and preventing them. The purpose of this study is to outline the commercial banks' place in terrorist financing processes by presenting their inherent characteristics within the scope of the Special Act on Measures Against Financing of Terrorism. У процесі глобалізації необхідність блокування фінансових потоків у терористичні організації стає все більш відчутною. Боротьба з фінансуванням тероризму стає національним і наднаціональним пріоритетом, а кредитні установи є одним з основних механізмів здійснення таких злочинів і тому охоплюються численними положеннями та інститутами, що стосуються їх ролі в контролі та їх запобіганню. Мета цього дослідження – описати місце комерційних банків у процесах фінансування тероризму, представивши їх невід'ємні характеристики в рамках Спеціального закону про заходи щодо фінансування тероризму. В процессе глобализации необходимость блокирования финансовых потоков в террористические организации становится все более ощутимой. Борьба с финансированием терроризма становится национальным и наднациональным приоритетом, а кредитные учреждения являются одним из основных механизмов совершения таких преступлений и поэтому охватываются многочисленными положениями и институтами, касающимися их роли в контроле и их предотвращении. Цель этого исследования – описать место коммерческих банков в процессах финансирования терроризма, представив их неотъемлемые характеристики в рамках Специального закона о мерах по финансированию терроризма.